Characterization of Experimental Short-Fiber-Reinforced Dual-Cure Core Build-Up Resin Composites - Säilynoja Eija; Garoushi Sufuan; Vallittu Pekka K; Lassila Lippo (Switzerland, 2022)
As a core build-up material, dual-cured (DC) resin-based composites are becoming popular. The aim of this research was to investigate specific physical and handling properties of new experimental short-fiber-reinforced DC resin composites (SFRCs) in comparison to different commercial, conventional DC materials (e.g., Gradia Core, Rebilda DC, LuxaCore Z, and Visalys® CemCore). Degree of monomer conversion (DC%) was determined by FTIR-spectrometry using either self- or light-curing mode. The flexural strength, modulus, and fracture toughness were calculated through a three-point bending setup. Viscosity was analyzed at room (22 °C) and mouth (35 °C) temperatures with a rotating disk rheometer. The surface microstructure of each resin composite was examined with scanning electron microscopy (SEM). Data were statistically analyzed with analysis of variance ANOVA (p = 0.05). The curing mode showed significant (p < 0.05) effect on the DC% and flexural properties of tested DC resin composites and differences were material dependent. SFRC exhibited the highest fracture toughness (2.3 MPa m1/2) values and LuxaCore showed the lowest values (1 MPa m1/2) among the tested materials (p < 0.05). After light curing, Gradia Core and SFRCs showed the highest flexural properties (p < 0.05), while the other resin composites had comparable values. The novel DC short-fiber-reinforced core build-up resin composite demonstrated super fracture toughness compared to the tested DC conventional resin composites.